2015
DOI: 10.14814/phy2.12480
|View full text |Cite
|
Sign up to set email alerts
|

Thick airway surface liquid volume and weak mucin expression in pendrin-deficient human airway epithelia

Abstract: Pendrin is an anion exchanger whose mutations are known to cause hearing loss. However, recent data support the linkage between pendrin expression and airway diseases, such as asthma. To evaluate the role of pendrin in the regulation of the airway surface liquid (ASL) volume and mucin expression, we investigated the function and expression of pendrin and ion channels and anion exchangers. Human nasal epithelial cells were cultured from 16 deaf patients carrying pendrin mutations (DFNB4) and 17 controls. The ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Similar results were found in HBE and CFBE cultures. Quantitative PCR analysis indicated that pendrin transcript levels were increased by 30-to 35-fold in the HBE and CFBE cultures (data not shown), similar to fold increases previously reported in similar cell systems (24,25,35).…”
Section: Specificity Of Pds Inh -A01 In Human Airway Epithelial Cell supporting
confidence: 87%
See 2 more Smart Citations
“…Similar results were found in HBE and CFBE cultures. Quantitative PCR analysis indicated that pendrin transcript levels were increased by 30-to 35-fold in the HBE and CFBE cultures (data not shown), similar to fold increases previously reported in similar cell systems (24,25,35).…”
Section: Specificity Of Pds Inh -A01 In Human Airway Epithelial Cell supporting
confidence: 87%
“…This observation is in agreement with the absence of pendrin function and low pendrin transcript expression found here and in a prior study (24). A prior study that investigated ASL depth homeostasis in airway cell cultures from subjects with pendrin loss-of-function mutations showed that ASL depth was increased by approximately 2-fold compared to cultures derived from control subjects, both without and with IL-13 (35). A possible explanation for the difference in results is that pendrin loss of function in DFNB4 subjects produces compensatory changes in gene expression or protein function that may alter ASL depth homeostasis.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, NIS expression has been localized to ciliated columnar cells of the bronchial mucosa, although its precise localization remains controversial (Kang et al 2009). Moreover, ANO1, CFTR, PENDRIN and DUOX2/ DUOX1 are expressed in the Ap membrane of bronchial epithelial cells (Lee et al 2015, Brennan et al 2016, and LPO is secreted primarily in tracheal and bronchial submucosal glands (Wijkstrom-Frei et al 2003). This situation…”
Section: Airwaysmentioning
confidence: 99%
“…Variants in SLC26A9 have been previously associated with atypical CF-like lung disease and risk for asthma (20,21) and modulation of airway response to CFTR-directed therapeutics (22,23). SLC26A9 has been reported to be expressed in epithelial cells of the lung and stomach and multiple other tissues, including salivary gland, heart, skin, kidney, thyroid, and prostate (10,13,(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%